Green hydrothermal synthesis of titanium dioxide and estimation of some of its microscopic and optical properties - Md. Kawsar; Md. Sahadat Hossain; Muhammad Shahriar Bashar; Md. Farhad Ali; Newaz Mohammed Bahadur; Samina Ahmed (Results in Surfaces and Interfaces)
In this study, TiO2 (Anatase) was synthesized from plant leaves like Aloe vera, Azadirachta indica, and Psidium guajava by hydrothermal method. The generated anatase was analyzed using various characterization methods, which include Thermogravimetric Analysis, X-ray Diffraction, Fourier Transform Infrared Spectroscopy, Scanning Electron Microscopy, Energy Dispersive X-ray Spectroscopy, and Ultraviolet–Visible Spectroscopy. From the TGA analysis, it is evident that the synthesized TiO2 shows a distinctive mass loss at three different temperatures, namely below 200 °C, 200-500 °C, and over 500 °C. At higher temperatures, a thermal stable phase is observed. The crystallite size of TiO2 samples has been determined using various mathematical methods., including Monshi-Scherrer Method, Williamson-Hall Method, Size-Strain Plot Method, Halder-Wagner Method, and Sahadat-Scherrer Method. The Williamson-Hall Method has been diversified, focusing on the Uniform stress deformation model, the Uniform deformation model, and the Uniform deformation energy density models. The synthesized anatase's crystallite size is within the acceptable range of <50 nm. Furthermore, the values for strain (−0.0133 to 0.0025), stress (−3 × 109 to 5 × 108 N/m2), as well as energy density (28.29–65.20 J/m3) were also estimated for the generated product. The EDX analysis confirms the stoichiometric purity of anatase, with a consistent chemical composition of 54.16–63.13 wt% titanium and 36.87 to 45.75 wt% oxygen across all samples, consistent with Rietveld analysis data. The optical band gaps of the produced anatase were determined as 5.54 eV for Aloe vera, 5.50 eV for Azadirachta indica, and 5.51 eV for Psidium guajava, respectively.